Response of Wheat Cultivars in Different Agricultural Practices Differed by Sowing Date - Acharya, Ramesh; Marahatta, Santosh; Amgain, Lal P (International Journal of Applied Sciences and Biotechnology, 2017)
A field experiment with three wheat varieties at different sowing dates on two crop establishment methods was accomplished to identify the optimum sowing date at AFU Rampur during winter season of 2014/2015. Three wheat varieties namely: Tillotama, Danfe and Vijay sown on three dates: 14th November, 29th November, and 14th December under two crop establishment practices: Conservational and conventional agriculture were evaluated with strip –split plot design in three replications. The field data onyield attributes and yields were collected. Earlier sowing on 14th November gave the highest yield (3427.15 kg ha-1), total dry matter (8154.44 kg ha-1), with longest days to crop maturation (133.11 days). In case of varieties, Vijay gave the highest grain yield (3458.61 kg ha-1) and total dry weight (4456.11 and 8832.42 kg ha-1 respectively) with earliest days to heading and maturity. The straw yield was the highest for 29th November sowing (5821 kg ha-1) and for Danfe variety (5756 kg ha-1). Vijay variety recorded the highest test weight (43.60 g) and highest harvest index (35.89%) even though with the lowest effective tillers per square meter (320.83), it proved to be the most promising variety. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 250-255